2017
DOI: 10.21009/jrpk.072.06
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Metode Praktikum IPA Berbasis Science Writing Heuristic (SWH) dan Motivasi Berprestasi Terhadap Hasil Belajar Kognitif Peserta Didik

Abstract: Penelitian ini bertujuan untuk menganalisis pengaruh metode praktikum IPA berbasis SWH dan motivasi berprestasi peserta didik terhadap hasil belajar IPA di kelas 7 pada materi Sifat dan Perubahan Fisika dan Kimia. Penerapan metode praktikum IPA berbasis Science Writing Heuristic (SWH) dan motivasi berprestasi merupakan pendekatan yang berperan dalam mendukung proses pembelajaran. Penelitian dilakukan pada bulan Oktober 2015-Juni tahun 2016 di salah satu SMP swasta yang ada di Bekasi. Metode penelitian yang dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Students do it in a fun way, so without realizing it, learning to write can be well absorbed. Retnosari [17] reinforced his research that based on the results of the study it was concluded that the application of the Science Writing Heuristic (SWH)-based Science practicum method in learning provided higher cognitive learning outcomes for students compared to conventional practicum methods on the subject of Nature and Changes in Material.…”
Section: Resultsmentioning
confidence: 87%
“…Students do it in a fun way, so without realizing it, learning to write can be well absorbed. Retnosari [17] reinforced his research that based on the results of the study it was concluded that the application of the Science Writing Heuristic (SWH)-based Science practicum method in learning provided higher cognitive learning outcomes for students compared to conventional practicum methods on the subject of Nature and Changes in Material.…”
Section: Resultsmentioning
confidence: 87%